Pengembangan Media Pembelajaran Matematika Video Interaktif berbasis Multimedia - Putri Utami Suseno; Yamin Ismail; Sumarno Ismail (Jambura Journal of Mathematics Education, 2020)
This article discusses the development of mathematics learning media in the form of interactive multimedia-based videos. Media development was carried out for learning flat-plane geometry on the topic of kites. The media development method used a descriptive approach through 3 stages, namely defining, designing, and developing by involving students of SMP Negeri 3 Gorontalo as research subjects. The multimedia-based interactive video learning media produced was declared valid based on expert judgment both in terms of media and on material substance. In its application, there was a positive response from more than 70% of students who took part in the learning process. This shows that the multimedia-based interactive video learning media is good and suitable for use as a medium for learning mathematics.